Tanggung jawab anak remaja kristen jemaat gki pengharapan jayapura dalam menjaga lingkungan berdasarkan kejadian 1: The responsibility of Christian teenagers of the gki gki jayapura hope congregation in protecting the environment based on genesis 1 - TEFBANA, APRI (MURAI: Jurnal Papua Teologi Konstekstual, 2025)
Climate change and environmental degradation have become one of the pressing issues in the city of Jayapura, and the contribution of Christian adolescents is crucial in caring for and preserving the environment. The level of awareness of Christian adolescents in maintaining and caring for their living environment is often still lacking. In this situation, the teachings of God's word in the church can provide important moral insights or directions. The teachings of God's word sourced from the Bible emphasize the importance of Christian teenagers to protect and care for God's created environment, including nature and its isis. This study aims to examine the responsibilities of Christian adolescents and the role of Christian adolescents in caring for God's creation. This research method uses a qualitative approach with literature studies. The literature method is used to collect information and data through literature, notebooks, reference journals and relevant research. The results of this study increase the knowledge and awareness of Christian adolescents about their responsibilities in protecting the environment as a form of worship to God in daily life.